To solve the equation step by step, let's start with the given expression:
\[ 10 \left(\frac{1}{2}x + 2\right) - 5 = 3(x - 6) + 1 \]
-
Apply the Distributive Property:
Left side: \[ 10 \left(\frac{1}{2}x + 2\right) = 10 \cdot \frac{1}{2}x + 10 \cdot 2 = 5x + 20 \]
The left side becomes: \[ 5x + 20 - 5 = 5x + 15 \]
Right side: \[ 3(x - 6) + 1 = 3x - 18 + 1 = 3x - 17 \]
So the equation now is: \[ 5x + 15 = 3x - 17 \]
-
Combine Like Terms:
To isolate \( x \), subtract \( 3x \) from both sides: \[ 5x - 3x + 15 = -17 \] This simplifies to: \[ 2x + 15 = -17 \]
-
Isolate the Variable Term:
Next, subtract 15 from both sides: \[ 2x + 15 - 15 = -17 - 15 \] Which simplifies to: \[ 2x = -32 \]
-
Solve for x:
Divide both sides by 2: \[ x = \frac{-32}{2} = -16 \]
Now, we have the solution \( x = -16 \).
- Possible Coefficients of x:
Next, we look at the coefficients based on the steps that Lorie completed. Before the final operation where we divided by 2, we could have potential coefficients \(-32\) (from \(2x\) resulting in \(-32\)) and \(2\) (already present as the coefficient of \(x\) before moving through the steps).
Thus, the possible coefficients of \( x \) after Lorie has completed these steps are: \[ -32 \text{ and } 2 \]
From the options presented in your question, the correct answer is:
–32 and 2.